The Protective Effect of Andrographis paniculata Against Lipopolysaccharide-induced Sepsis in Lung Tissues of a Rat Model Through the Decrease of ICAM-1 and E-selectin Expression - Michael Kevin; Nyoman Suci Widyastiti; Selamat Budijitno; Yan Wisnu Prajoko; Neni Susilaningsih (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Andrographis paniculata has anti-inflammatory, anti-cancer, and immunomodulatory effects. Intercellular adhesion molecule-1 (ICAM-1) and E-selectin are released in inflammatory conditions due to sepsis. In sepsis-associated fatalities, E-selectin is strongly expressed on pulmonary microvasculature and ICAM-1 is strongly expressed on pulmonary microvasculature endothelial cells, pulmonary macrophages, and lymphocytes. Therefore, this study was conducted to analyze the protective effect of A. paniculata leaf extract against lung injury in lipopolysaccharide (LPS)-induced sepsis mouse model.METHODS: Thirty male Wistar rats were divided into 1 control group and 4 sepsis groups. The control group was fed ad libitum for 14 days, followed by an intraperitoneal injection of 5 mg/kgBW 0.9% NaCl on day-21. While the sepsis groups were fed ad libitum and orally administered 0, 200, 400, and 500 mg/kgBW of A. paniculata leaf extract, respectively, for 14 days. All four sepsis groups were intraperitoneally injected with 5 mg/kgBW LPS on day-21. Mice termination and measurement of ICAM-1 and E-selectin were performed on day-25. The immunohistochemical examination of ICAM-1 expression was performed using ICAM-1/CD54 antibody, meanwhile E-selectin expression was examined using primary antibody E-Selectin (D-7) rabbit IgG antibody. RESULTS: All groups given A. paniculata leaf extract showed lower expression of ICAM-1 (p<0.001) and E-selectin (p<0.001) than the group without extract. A. paniculata leaf extract 500 mg/kgBW gives the best effectiveness compared to other doses.CONCLUSION: A. paniculata leaf extract has a protective effect against lung injury by lowering the expression of ICAM-1 and E-selectin in lung tissue.KEYWORDS: ICAM-1, E-selectin, sepsis, Andrographis paniculata, andrographolide